Expression of Carboxypeptidase A3 and Tryptase as Markers for Lymph Node Metastasis of Canine Cutaneous Mast Cell Tumors - Thaiwong, Tuddow; Cirillo, Juliana V.; Heller, Jane; Kiupel, Matti (Frontiers in Veterinary Science, 2022)
Detection of metastatic mast cell tumors (MCTs) in lymph nodes is a critical factor for treatment, prognosis, and clinical management. Presence/absence of mast cells in the lymph nodes cannot be used as a sole parameter to determine metastasis due to the inability to differentiate neoplastic from non-neoplastic/inflammatory mast cells. While cytologic and histopathologic classifications for assessment of metastatic MCTs based on the numbers and distribution of mast cells have been developed, inconsistency between the clinical interpretation of these grading schemes and actual metastatic status occurs. The aim of this study is to identify a novel diagnostic tool to accurately predict overt metastatic mast cell tumors in lymph nodes. We investigated the possibility of using RT-qPCR to detect mRNA expression of mast cell-specific genes in lymph nodes with different stages of MCT metastatic classification. We are able to establish a highly sensitive and discriminating RT-qPCR measuring Carboxy peptidase A3 (CPA3) and tryptase mRNA expression and identify the cut-off values with high sensitivity and specificity for overt metastatic MCTs in lymph nodes. An area of future interest would be to expand our analysis of the extent to which cut-off values for these markers in correctly identifying disease status, as well as predicting clinical outcomes and survival times. This would offer valuable information regarding the practical applicability of this technique and may enable us to improve our standards of detection metastasis, including possibility of molecular analysis of cytologic specimens obtained from suspicious nodes subjected to surgical excision.